R code to reproduce analyses of exotic plant invasion in fragmented and continuous forest sites in Sabah, Malaysian Borneo, 2017 - Waddell, E.H.; Chapman, D.S. (NERC Environmental Information Data Centre, 2020)
This code uses pathway modelling to look at correlations of exotic plant invasion in tropical rainforest remnants and continuous sites. Partial least squares path-modelling looks at correlations between latent variables that are informed by measured variables. The code examines the relative influence of landscape-level fragmentation, local forest disturbance, propagule pressure, soil characteristics and native community composition on invasion. The total native community is examined first. Then subsets of the native community are modelled separately, adult trees, tree saplings, tree seedlings and ground vegetation. The relationship between the native and exotic communities was tested in both directions.
The fieldwork for this study took place in fragmented and continuous forest sites in Sabah, Malaysian Borneo from July to October 2017. Native and exotic plants were surveyed in a nested plot design to determine genera richness and abundance. Phylogenetic diversity was calculated for the total native community and separately for adult trees, tree saplings, tree seedlings and ground vegetation. Phylogenetic diversity, genera richness and abundance made up the 'Native community' latent variable for the pathway modelling. 'Invasion' latent variable was informed by the species richness and abundance of exotic plants found in each plot. 'Fragmentation' latent variable was informed by the number of years since first planting of oil palm, the amount of non-forest area and the forest edge to forest area ratio within a 2km radius buffer of each plot. 'Disturbance' latent variable was informed the number of large trees belonging to Dipterocarpaceae and the the average adult tree wood density per plot. "Propagule pressure' latent variable was informed the number of exotic species and individuals found outside the forest over two 100m transect in the oil palm. 'Soil characteristics' latent variable was informed by soil pH and available Phosphorus in the topsoil of each plot. Connections between latent variables were informed by ecological theory and made up the full model. This included Fragmentation influencing Disturbance, Propagule pressure, Soil characteristics, Native community and Invasion. Disturbance influenced Soil characteristics, Native community and Invasion. Soil characteristics influenced the Native community and Invasion. Both the Native community and Propagule pressure influenced Invasion only. Invasion influenced just the Native community. Non-significant connections were removed in a step-wise manner before the final path-model was produced with significant correlations.
Keywords: Borneo; Agriculture; Biodiversity; Invasive species; Land cover; Land use; Soil; Agricultural landscapes; Roundtable on Sustainable Palm Oil; Sustainable agriculture; Forest fragmentation; Logging; Forest degradation; Non-native species; Oil palm; Conservation set-aside; tropical forest; flora (biology); forest conservation; agriculture; environmental impact of agriculture; degradation